Analgosedierung in der Kardiologie - Konsensuspapier der DGK und DGAI 2024 - Tilz, Roland R.; Busch, Sonia; Chun, K. R.J.; Frerker, Christian; Gaede, Luise; Steven, Daniel; Tiefenbacher, Christiane; Eckardt, Lars; Sander, Michael; Zwißler, Bernhard; Wappler, Frank; von Dossow, Vera; et al. (Die Kardiologie, 2024)
Interventions in electrophysiology and interventional cardiology are increasingly common. Many of these interventions are performed under sedation. This is necessary to ensure the patient’s comfort and safety to facilitate transesophageal echocardiography, pain control, or long procedure duration, e.g., with stable mapping conditions. This consensus document by the German Cardiac Society (DGK) together with the German Association of Anesthesia and Intensive Care (DGAI) describes—based on current evidence—the structured pathways for sedation in cardiovascular medicine. The major goal is patient safety for patients undergoing electrophysiology and endovascular cardiovascular procedures. This consensus document is also aligned to the published German S3 guideline for sedation in gastroenterology.
CRIS-Team Scopus Importer:2024-03-08
Keywords: Atrial fibrillation; Catheter ablation; Defibrillators; implantable; Mitraclip; Pacemaker; artificial